A Julia package for Polyhedral Omega and applications - Ayyıldız, Tülay; Demirel, Deniz Naz; Tapan, Ismail; Zafeirakopoulos, Zafeirakis (Assoc Computing Machinery, 2024)
This paper introduces a Julia package for tackling linear Diophantine systems and related optimization problems using the Polyhedral Omega algorithm. The package integrates partition analysis and polyhedral geometry to offer efficient solutions. PolyhedralOmega.jl package implements the Polyhedral Omega algorithm, and Optimization.jl provides optimization enhancements.